PENGARUH KOMPENSASI RUGI FISKAL, KONEKSI POLITIK DAN REFORMASI PERPAJAKAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Theruty, Nadya Ingrida; Lindrawati, Lindrawati (Jurnal Akuntansi Kontemporer, 2015)
Tax is one of the most important fund for our country. That is why our government try to improve its revenue from taxes. However, some companies see taxes as something they should avoid, so that is why they do tax avoidance. For determine tax avoid-ance, we can use earnings tax rate (ETR). The purpose of this research was to examine and analyze effect of loss carry-forward, political connections and tax reform of tax avoidance. The research design was quantitative with the hypothesis. The data in the form of quantitative research in the form of an financial report period 2008-2012. The object of research is a manufacture company that is listed on the Indonesia Stock Exchange 2008-2012 period. Data were analyzed using multiple linear regression analysis. The analy-sis showed that the loss carry-forward has significant positive effect on the tax avoidance , political connection has no significant effect on the tax avoidance and tax reform has significant negative effect on the tax avoidance. It is shows that the last tax reform that happen at 2008 reduce the will of the company to do tax avoidance because there is a change in tax tariff.